Capitalization of operating leases and the cost of bank loans - Golden, Joanna; Liu, Xiaotao Kelvin (Journal of Corporate Finance, 2025)
This study investigates whether the cost of bank loans is associated with the adoption of new lease standards, which mandate firms to recognize operating leases and increase disclosures. Consistent with our hypothesis, we find robust evidence that treatment firms (i.e., borrowers with higher operating leases in the pre-implementation period) are associated with a greater decline in loan spreads. The effect is more pronounced among unrated firms, borrowers with more opaque pre-implementation financial disclosure, and loans syndicated by less sophisticated lenders. We also document that treatment firms are associated with a greater increase in the number of lenders, debt maturity, and credit ratings. Moreover, treatment firms experience a greater reduction in covenant intensity and covenant tightness. Collectively, our evidence suggests that compliance with ASC 842 improves the reporting reliability and disclosure quality of operating leases.